Labrador Inuttitut: Speaking into the future - Andersen, Catharyn; Johns, Alana (Études/Inuit/Studies, 2005)
AbstractThis paper discusses the issue of language loss in northern Labrador Inuttitut. Like many communities across northern Canada, Labrador is facing the possible complete loss of Inuktitut, demonstrated by the fact that almost no children speak it as a first language any longer. In this paper we outline a number of linguistic properties which make Labrador Inuttitut and a related dialect spoken in Rigolet distinct from neighbouring dialects of Inuktitut. We also report on a number of initiatives taken up by community organizations, school and individuals in their growing efforts to reverse language shift. These include a language survey, dictionaries, youth camps, a language nest, etc.